The Potential for Ketogenic Diets to Control Glucotoxicity, Hyperinsulinemia, and Insulin Resistance to Improve Fertility in Women with Polycystic Ovary Syndrome - Leticia Ramírez-Martínez; Cecilia Palafox-Gómez; Leonardo M. Porchia; Esther López-Bayghen (Clinical and Experimental Obstetrics & Gynecology)
Objective: This review aims to summarize the association between insulin resistance (IR) and symptoms of Polycystic Ovary Syndrome (PCOS) while explaining how nutritional interventions, specifically ketogenic diets, help manage PCOS. Mechanism: The effect of IR on diagnostic criteria for PCOS is first described, followed by how a standard diet exacerbates IR. Afterward, nutritional interventions, specifically for women with PCOS, are described. Findings in Brief: IR is associated with ovulatory dysfunction, hyperandrogenism, and polycystic ovarian morphology, which leads to metabolic abnormalities and loss of fertility. Activation of the polyol pathway, advanced glycation end-product accumulation, and hexosamine flux by hyperglycemia and IR are involved in the PCOS phenotypes and reproduction alterations. IR affects oocytes, ovaries, and the endometrium among women with PCOS, leading to infertility. However, nutritional interventions, specifically ketogenic diets, were shown to lower serum cholesterol, triglycerides, androstenedione, testosterone and attenuate IR. At the same time, high-density lipoprotein increased, promoting menstrual regularity and, eventually, providing a better environment for in vitro fertilization. Conclusion: For women with PCOS, managing IR is essential for managing their symptoms and improving fertility. Resolving glucotoxicity caused by excessive dietary glucose with a ketogenic diet is crucial for the prevention and correction of the damage associated with hyperinsulinemia and hyperglycemia, contributing to fertility.